Microwave absorption properties of rare earth (RE) ions doped Mn–Ni–Zn nanoferrites (RE = Dy, Sm, Ce, Er) to shield electromagnetic interference (EMI) in X-band frequency. Issue 22 (15th November 2022) - Srinivas, Ch; Naga Praveen, K.; Ranjith Kumar, E.; Singh, Surendra; Singh Meena, Sher; Bhatt, Pramod; Chandrasekhar Rao, T.V.; Sarkar, Debashish; Arun, B.; James Raju, K.C.; Sastry, D.L.
Abstract: Sol-gel auto combustion technique has been adopted to prepare RE doped Mn–Ni–Zn ferrite systems following the stoichiometry Mn0.1 Ni0.7 Zn0.2 RE0.5 Fe1.5 O4 (RE = Dy, Ce, Sm and Er). The XRD patterns confirm the cubic spinel phase with the Fd3m space group and the lattice parameter and crystallite size were found to be in the range of 8.3874–8.4066 Å and 28.6–33.2 nm. The M − H data indicates the soft magnetic behaviour of present ferrite systems. The substitution of rare-earth ions in the spinel structure influences the superexchange interaction and in turn, affects the magnetic behaviour of present ferrite systems. The highest value of saturation magnetization equal to 41.2 emu/g was observed for the sample with a composition of Mn0.1 Ni0.7 Zn0.2 Ce0.5 Fe1.5 O4 . For all the ferrite systems studied here the real part ( ε ′ ) of complex permittivity is increasing with an increase in frequency while oscillatory nature can be found in the imaginary part ( ε ″ ). The value of ε ′ found in the range of 5.421–5.856 at 8.2 GHz and it is 5.538–6.066 at 12.4 GHz. The value of ε ″ is in the range of 0.092–0.104 at 8.2 GHz while it is in between 0.042 and 0.105 at 12.4 GHz. A wavy nature can be seen in the real part ( μ ′ ) of complex permeability whereas the imaginary part ( μ ″ ) is decreasing for all compositions with the increase in frequency, but shows a weak resonance peak between 9 and 10 GHz. The value of μ ′ is in the range of 0.869–0.958 at 8.2 GHz and it is 0.903–0.925 at 12.4 GHz. The value of μ ″ fall in between 0.269 and 0.334 at 8.2 GHz and it is in the range of 0.059–0.068 at 12.4 GHz. The shielding studies for EMI revealed that the present systems are working as microwave absorbers. The total effective shielding for all ferrite systems is in the range of 33.31–36.09 dB 8.2 GHz while it is in between 32.74 and 34.98 dB at 12.4 GHz. Under the investigation of shielding performance, it is observed that all the RE doped Mn–Ni–Zn ferrites systems studied here can effectively suppress the electromagnetic interference in X-band frequency. The ferrite system with composition Mn0.1 Ni0.7 Zn0.2 Ce0.5 Fe1.5 O4 has shown a potential microwave absorber in X-band frequency.